The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.18356/8be4e79e-en
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality in Brazil: What has changed in recent years?

Abstract: This paper provides empirical evidence to assess the impact of socioeconomic and political variables on different measures of income inequality based on the 27 units of the Brazilian federation in the period from 1999 to 2008. The Brazilian experience is a good example for understanding the income inequality policies in developing countries. The findings suggest that the improvement observed along the period under analysis is a result of the combination of increased trade openness, technological and financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The corruption can raise the income inequality by considering the suggestions of Gupta et al (1998) and the large part of existing empirical literature verified the theoretical considerations (e.g. see Apergis et al, 2010;Dwiputri et al, 2018;Ferreira de Mendonça and Martins Esteves, 2014;Huang, 2013;Mehrara et al, 2011). However, Rodriguez Andres and Ramlogan- Dobson (2008), Dobson and Ramlogan-Dobson (2010) and Dobson and Ramlogan-Dobson (2012) reached the opposite findings for Latin American countries and they evaluated that this finding may result from a relatively higher shadow economy, but de Ferreira de Mendonça and Martins Esteves (2014) revealed that improvements in the corruption decreased the income inequality in 27 Brazilian regions.…”
Section: Westerlund and Edgerton (2007) Lm Bootstrap Cointegration Testmentioning
confidence: 85%
See 3 more Smart Citations
“…The corruption can raise the income inequality by considering the suggestions of Gupta et al (1998) and the large part of existing empirical literature verified the theoretical considerations (e.g. see Apergis et al, 2010;Dwiputri et al, 2018;Ferreira de Mendonça and Martins Esteves, 2014;Huang, 2013;Mehrara et al, 2011). However, Rodriguez Andres and Ramlogan- Dobson (2008), Dobson and Ramlogan-Dobson (2010) and Dobson and Ramlogan-Dobson (2012) reached the opposite findings for Latin American countries and they evaluated that this finding may result from a relatively higher shadow economy, but de Ferreira de Mendonça and Martins Esteves (2014) revealed that improvements in the corruption decreased the income inequality in 27 Brazilian regions.…”
Section: Westerlund and Edgerton (2007) Lm Bootstrap Cointegration Testmentioning
confidence: 85%
“…There have been extensive studies on the inflation-inequality nexus and unemployment-inequality nexus, but a limited number of studies have investigated the interaction between the misery index, consisting of both inflation and unemployment, and income inequality. The papers examining the interaction between the inflation-inequality nexus have reached mixed findings, while most of the studies have revealed a positive relationship between unemployment and income inequality or a negative relationship between employment and income inequality (e.g., see Apergis et al, 2010;Bulir, 2001;Ferreira de Mendonça and Martins Esteves, 2014;Monnin, 2014;Rice and Lozada, 1983;Thalassinos et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the target population for social benefits is key to understanding the role of public spending on income inequality. Consider, for example, the case of Brazil, where social transfers contribute to increasing income inequality because these resources may not be reaching the poorest families (Ferreira de Mendonça and Martins Esteves 2014). As a result, non-contributory social assistance has gained prominence as a fundamental instrument to mitigate the ascending trend of market income inequality in many developing countries (Obi and Ndhleve 2011;Tekgüç 2018).…”
Section: Social Protectionmentioning
confidence: 99%